2022
DOI: 10.55927/eajmr.v1i8.1266
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Market Orientation, Entrepreneurial Orientation, Knowledge Management and Learning Organization on Performance Mediated by Innovation in Culinary SME’s in Bekasi

Abstract: This study aims to see the effect of innovation mediation that connects market orientation, entrepreneurial orientation, knowledge management and organization learning on the performance of MSMEs in the city of North Bekasi. This study uses a quantitative. The unit of analysis in this study is the Culinary SMEs in North Bekasi. This research was conducted on 231 respondents spread across northern Bekasi and used the SmartPLS 3.3.3 statistical tools. The results of this study further emphasize that innovation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
(39 reference statements)
0
5
0
7
Order By: Relevance
“…The previous empirical research evidence regarding the influence of learning orientation on MSME performance was carried out by Rosli and Sidek (2013), Hafeez et al (2012), Eshlaghy and Maatofi (2011), Eris et al (2012) and Abiodun and Kida (2016) concluded that learning orientation has an influence on the performance of MSMEs. Different results were shown by Nursal et al (2022) and Suliyanto and Rahab (2012), who concluded that learning orientation had no influence on the performance of MSMEs. Based on several previous research results regarding the influence of learning orientation on the performance of MSMEs, there are still differences in results (research gaps), thus opening a gap to re-examine the influence of learning orientation on the performance of MSMEs with innovation capabilities as a mediator.…”
Section: Figure 1 Foreign Tourist Visits Per Yearmentioning
confidence: 79%
“…The previous empirical research evidence regarding the influence of learning orientation on MSME performance was carried out by Rosli and Sidek (2013), Hafeez et al (2012), Eshlaghy and Maatofi (2011), Eris et al (2012) and Abiodun and Kida (2016) concluded that learning orientation has an influence on the performance of MSMEs. Different results were shown by Nursal et al (2022) and Suliyanto and Rahab (2012), who concluded that learning orientation had no influence on the performance of MSMEs. Based on several previous research results regarding the influence of learning orientation on the performance of MSMEs, there are still differences in results (research gaps), thus opening a gap to re-examine the influence of learning orientation on the performance of MSMEs with innovation capabilities as a mediator.…”
Section: Figure 1 Foreign Tourist Visits Per Yearmentioning
confidence: 79%
“…Intesitas persaingan diadopsi dari penelitian (Suryawan, 2020) dengan 3 item pernyataan. Inovasi diadopsi dari penelitian (Nursal et al, 2022) dengan 7 item pernyataan serta kinerja diadopsi dari penelitian (Rianto et al, 2021) dengan 7 item pernyataan. Penelitian ini menggunakan alat statistik smartpls 4.0 dengan menggunakan dua analisis.…”
Section: Metode Penelitianunclassified
“…Hasil yang telah ditunjukkan diatas menggambarkan bahwa adanya pengaruh orientasi kewirausahaan terhadap inovasi penelitian ini sejalan dengan penelitian sebelumnya (Nursal et al, 2022) dengan adanya orientasi kewirausahaan UMKM memiliki kemampuan untuk menemukan produk atau layanan baru (inovasi) sebagai keunggulan bersaing. Peranan perempuan muslim yang memiliki pondasi jiwa kewirausahaan yang kuat telah dicontohkan oleh nabi Muhammad yang pernah menjadi pedagang dalam sejarah Islam.…”
Section: Pembahasanunclassified
See 2 more Smart Citations